Social and family life impact of shift work from the perspective of family members - Costa, Daniela (2019)
Research has thus far privileged the impact of shift work on workers' health from the workers' perspective. Inversely, this study evaluates the impacts of such a work schedule on the family and social life of workers according to their partners' perspective. It also compared the impacts of two different work schedules (shift work vs. normal work) on family and social life. Five hundred and fifteen partners of Portuguese police officers participated in the study, and it was found that shift work has a moderate to high impact on all evaluated areas of family and social life. Partners of shift workers report greater impacts on family reorganization and joint social life. Regarding the two work schedules, statistically significant differences were found in all evaluated areas, and the partners of shift workers reported greater impacts of their partner's work schedule than did the partners of day workers.